Interlaced influence of arbuscular mycorrhiza and water management on mite infestation and kohlrabi production - Mohammed, Alaa F.; shatoury, Rewaa. S. El; Kamel, Marwa S.; Mahmoud, Amr K. (Agriculture and Natural Resources, 2019)
An experiment was conducted to assess the influence of arbuscular mycorrhiza and water management on mite infestation and kohlrabi production. This study monitored the influence of three water quantity treatments (Q1, Q2, Q3) with averages of 180 mm, 270 mm and 360 mm, respectively, and two treatments of seed inoculation: 1) seeds inoculated by arbuscular mycorrhizal (AM) and, 2) seeds not inoculated by arbuscular mycorrhizal (Non-AM) on yield production, plant parameters, mite density, canopy temperature, water use and heat use efficiency. The results revealed that the mycorrhizal inoculation increased the yield production with a low amount of water (Q2) by approximately 55% compared to the other treatments with an irrigation water use efficiency of 7.54 kg/m3 and a heat use efficiency of 23.6 kg/ha/°C/d. Moreover, leaf chlorophyll concentration especially with the low amount of water (Q2) was 61%, which was the same as the net irrigation water requirement. The interaction between AM and Q2 was highly significant for mycorrhizal root colonization (71%), and had a positive effect on all plant parameters (plant length, leaf number, root length). Furthermore, predator and soil mites (Amblyseius swirskii, Euseius scutalis, Golumna tarsipennata, Zygoribatula tritici) had significant densities with the same interaction treatment. Noticeably, these results encouraged using AM inocula as “bio-enhancers” of plant performance in agricultural systems.